Air Pollution and the Dynamic Association Between Depressive Symptoms and Memory in Oldest‐Old Women. Issue 2 (17th November 2020) - Petkus, Andrew J.; Younan, Diana; Wang, Xinhui; Beavers, Daniel P.; Espeland, Mark A.; Gatz, Margaret; Gruenewald, Tara L.; Kaufman, Joel D.; Chui, Helena C.; Manson, JoAnn E.; Resnick, Susan M.; Wellenius, Gregory A.; et al.
Abstract : BACKGROUND/OBJECTIVES: Exposure to air pollution may contribute to both increasing depressive symptoms and decreasing episodic memory in older adulthood, but few studies have examined this hypothesis in a longitudinal context. Accordingly, we examined the association between air pollution and changes in depressive symptoms (DS) and episodic memory (EM) and their interrelationship in oldest‐old (aged 80 and older) women. DESIGN: Prospective cohort data from the Women's Health Initiative Memory Study‐Epidemiology of Cognitive Health Outcomes. SETTING: Geographically diverse community‐dwelling population. PARTICIPANTS: A total of 1, 583 dementia‐free women aged 80 and older. MEASUREMENTS: Women completed up to six annual memory assessments (latent composite of East Boston Memory Test and Telephone Interview for Cognitive Status) and the 15‐item Geriatric Depression Scale (GDS‐15). We estimated 3‐year average exposures to regional particulate matter with aerodynamic diameter below 2.5 μm (PM2.5 ) (interquartile range [IQR] = 3.35 μg/m 3 ) and gaseous nitrogen dioxide (NO2 ) (IQR = 9.55 ppb) at baseline and during a remote period 10 years earlier, using regionalized national universal kriging. RESULTS: Latent change structural equation models examined whether residing in areas with higher pollutant levels was associated with annual changes in standardized EM and DS while adjusting for potential confounders. Remote NO2 (β = .287 per IQR; P = .002) and PM2.5 (β = .170 per IQR; P = .019) exposure was significantly associated with larger increases in standardized DS, although the magnitude of the difference, less than 1 point on the GDS‐15, is of questionable clinical significance. Higher DS were associated with accelerated EM declines (β = −.372; P = .001), with a significant indirect effect of remote NO2 and PM2.5 exposure on EM declines mediated by DS. There were no other significant indirect exposure effects. CONCLUSION: These findings in oldest‐old women point to potential adverse effects of late‐life exposure to air pollution on subsequent interplay between DS and EM, highlighting air pollution as an environmental health risk factor for older women.